Protocol for a MULTI-centre feasibility study to assess the use of 99mTc-sestaMIBI SPECT/CT in the diagnosis of kidney tumours (MULTI-MIBI study). Issue 1 (24th January 2023) - Warren, Hannah; Wagner, Thomas; Gorin, Michael A; Rowe, Steven; Holman, Beverley Fiona; Pencharz, Deborah; El-Sheikh, Soha; Barod, Ravi; Patki, Prasad; Mumtaz, Faiz; Bex, Axel; Kasivisvanathan, Veeru; et al.
Abstract : Introduction: The incidence of renal tumours is increasing and anatomic imaging cannot reliably distinguish benign tumours from renal cell carcinoma. Up to 30% of renal tumours are benign, with oncocytomas the most common type. Biopsy has not been routinely adopted in many centres due to concerns surrounding non-diagnostic rate, bleeding and tumour seeding. As a result, benign masses are often unnecessarily surgically resected. 99m Tc-sestamibi SPECT/CT has shown high diagnostic accuracy for benign renal oncocytomas and other oncocytic renal neoplasms of low malignant potential in single-centre studies. The primary aim of MULTI-MIBI is to assess feasibility of a multicentre study of 99m Tc-sestamibi SPECT/CT against a reference standard of histopathology from surgical resection or biopsy. Secondary aims of the study include obtaining estimates of 99m Tc-sestamibi SPECT/CT sensitivity and specificity and to inform the design and conduct of a future definitive trial. Methods and analysis: A feasibility prospective multicentre study of participants with indeterminate, clinical T1 renal tumours to undergo 99m Tc-sestamibi SPECT/CT (index test) compared with histopathology from biopsy or surgical resection (reference test). Interpretation of the index and reference tests will be blinded to the results of the other. Recruitment rate as well as estimates of sensitivity, specificity, positive and negative predictive value will be reported. Semistructured interviews with patients and clinicians will provide qualitative data to inform onward trial design and delivery. Training materials for 99m Tc-sestamibi SPECT/CT interpretation will be developed, assessed and optimised. Early health economic modelling using a decision analytic approach for different diagnostic strategies will be performed to understand the potential cost-effectiveness of 99m Tc-sestamibi SPECT/CT. Ethics and dissemination: Ethical approval has been granted (UK HRA REC 20/YH/0279) protocol V.5.0 dated 21/6/2022. Study outputs will be presented and published nationally and internationally. Trial registration number: ISRCTN12572202 .